Accelerated aging: A marker for social factors resulting in cardiovascular events?. (March 2021) - Forrester, Sarah N.; Zmora, Rachel; Schreiner, Pamela J.; Jacobs, David R.; Roger, Veronique L.; Thorpe, Roland J.; Kiefe, Catarina I.
Abstract: Background: Medicine and public health are shifting away from a purely "personal responsibility" model of cardiovascular disease (CVD) prevention towards a societal view targeting social and environmental conditions and how these result in disease. Given the strong association between social conditions and CVD outcomes, we hypothesize that accelerated aging, measuring earlier health decline associated with chronological aging through a combination of biomarkers, may be a marker for the association between social conditions and CVD. Methods: We used data from the Coronary Artery Risk Development in Young Adults study (CARDIA). Accelerated aging was defined as the difference between biological and chronological age. Biological age was derived as a combination of 7 biomarkers (total cholesterol, HDL, glucose, BMI, CRP, FEV1/h 2, MAP), representing the physiological effect of "wear and tear" usually associated with chronological aging. We studied accelerated aging measured in 2005-06 as a mediator of the association between social factors measured in 2000-01 and 1) any incident CVD event; 2) stroke; and 3) all-cause mortality occurring from 2007 through 18. Results: Among 2978 middle-aged participants, mean (SD) accelerated aging was 3.6 (11.6) years, i.e., the CARDIA cohort appeared to be, on average, 3 years older than its chronological age. Accelerated aging partially mediated the association between social factors and CVD (N=219), stroke (N=36), and mortality (N=59). Accelerated aging mediated 41% of the total effects of racial discrimination on stroke after adjustment for covariates. Accelerated aging also mediated other relationships but to lesser degrees. Conclusion: We provide new evidence that accelerated aging based on easily measurable biomarkers may be a viable marker to partially explain how social factors can lead to cardiovascular outcomes and death. Highlights: Accelerated aging is consistent with a mediator between psychosocial stress and CVD. Accelerated aging mediates the association between racial discrimination and stroke. Accelerated aging may be a candidate mechanism for studying health disparities.